Effect of Vitamin D3 supplementation on symptomatic uterine leiomyoma in women with Hypovitaminosis D - Amita Suneja; Fahmina Faridi; Shuchi Bhatt; Kiran Guleria; Mohit Mehndiratta; Richa Sharma (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective of this study is to evaluate the effect of Vitamin D3 on symptoms, uterine and leiomyoma volume in women with symptomatic leiomyoma and hypovitaminosis D. Materials and Methods: In this pilot, interventional, prospective study, 30 premenopausal women with uterine leiomyoma and concomitant hypovitaminosis D (<30 ng/ml) received Vitamin D3 in doses of 60,000 IU weekly for 8 weeks followed by 60,000 IU every 2 weeks for another 8 weeks. Change in symptoms, uterine, and leiomyoma volume was evaluated at 8 weeks and 16 weeks. Serum Vitamin D3 levels were repeated at 16 weeks of therapy. Results: A significant negative correlation was observed between the baseline 25-hydroxy Vitamin D (25(OH) Vitamin D3) and leiomyoma volume (r = -0.434, P < 0.001). There was significant reduction of menstrual blood loss by 29.89% (P = 0.003) and severity of dysmenorrhea, pelvic pain, and backache by 44.12%, 35%, and 50% (P < 0.001, 0.019, and 0.002), respectively, at 16 weeks. At end of therapy, there was 6% reduction in mean uterine volume and 11% in leiomyoma volume which was not significant. Serum 25(OH) Vitamin D3 was significantly higher than baseline level (17.44 ± 5.82 vs. 39.38 ± 8.22, P < 0.001) at end of therapy. Conclusion: Vitamin D3 supplementation is effective in reducing leiomyoma-related symptoms and stabilizing uterine and leiomyoma volume.